Coral Covers and the Abundance of Reef Fish in Community Base Management Marine Protected Area (CBM-MPA) Bahoi Village North Sulawesi, Indonesia - Siahaan, Dedy Octavian; Mandagi, Stephanus V.; Wagey, Billy T.; Sumilat, Deiske A. (Jurnal Ilmiah Platax, 2023)
In the last few decades, coral reef ecosystem has been under significant pressure due to anthropogenic impacts and naturally driven factors. The coral reef ecosystem is unique because it has very high biodiversity and many organisms depend on its existence. Every organism in a coral reef ecosystem uniquely contributes to how coral reef communities survive and function. However, coral reef ecosystems are also vulnerable to pressures that cause degradation, interfering with the ecosystem balance. This study aims to monitor the ecological condition of coral reefs and the abundance of reef fish to see how the MPA program in Bahoi village helps the coral reef ecosystem from degradation. The data was collected using Line Intercept Transect (LIT) method, which was drawn 70 meters transect line horizontally at a depth of 3-5 meters. The same transect line was also used to collect data about reef fish by using a Visual Census. The observation distance length is 2.5 meters to the left and right of the transect line. Results of the study showed that the coral cover of MPA Bahoi Village is in the Fair category and the abundance of reef fish in the MPA area is in the Moderate category.  Keywords: Coral Cover; Coral Reef; Marine Protected Area (MPA); Monitoring; Reef Fish